Metformin Modulates T Cell Function and Alleviates Liver Injury Through Bioenergetic Regulation in Viral Hepatitis - Xu, Lanman; Wang, Xiaofang; Chen, Yan; Soong, Lynn; Chen, Yongping; Cai, Jiyang; Liang, Yuejin; Sun, Jiaren (Frontiers in Immunology, 2021)
Metformin is not only the first-line medication for the treatment of type 2 diabetes, but it is also effective as an anti-inflammatory, anti-oxidative and anti-tumor agent. However, the effect of metformin during viral hepatitis remains elusive. Using an adenovirus (Ad)-induced viral hepatitis mouse model, we found that metformin treatment significantly attenuated liver injury, with reduced serum aspartate transaminase (AST) and alanine transaminase (ALT) levels and liver histological changes, presumably via decreased effector T cell responses. We then demonstrated that metformin reduced mTORC1 activity in T cells from infected mice, as evidenced by decreased phosphorylation of ribosome protein S6 (p-S6). The inhibitory effects on the mTORC1 signaling by metformin was dependent on the tuberous sclerosis complex 1 (TSC1). Mechanistically, metformin treatment modulated the phosphorylation of dynamin-related protein 1 (Drp-1) and mitochondrial fission 1 protein (FIS1), resulting in increased mass in effector T cells. Moreover, metformin treatment promoted mitochondrial superoxide production, which can inhibit excessive T cell activation in viral hepatitis. Together, our results revealed a protective role and therapeutic potential of metformin against liver injury in acute viral hepatitis via modulating effector T cell activation via regulating the mTORC1 pathway and mitochondrial functions.